Formation of Twinned Graphene Polycrystals. Issue 23 (8th May 2019) - Dong, Jichen; Geng, Dechao; Liu, Fengning; Ding, Feng
Abstract: Liquid metals have been widely used as substrates to grow graphene and other 2D materials. On a homogeneous and isotropic liquid surface, a polycrystalline 2D material is formed by coalescence of many randomly nucleated single‐crystal islands, and as a result, the domains in a polycrystal are expected to be randomly aligned. Here, we report the unexpected finding that only 30°‐twinned graphene polycrystals are grown on a liquid Cu surface. Atomic simulations confirm that the unique domain alignment in graphene polycrystals is due to the free rotation of graphene islands on the liquid Cu surface and the highly stable 30°‐grain boundaries in graphene. In‐depth analysis predicts 30 types of possible 30°‐twinned graphene polycrystals and 27 of them are observed. The revealed formation mechanism of graphene polycrystals on a liquid Cu surface deepens our fundamental understanding on polycrystal growth and could serve as a guideline for the controlled synthesis of 2D materials. Abstract : Lucky twins : Based on a theoretical analysis of graphene chemical vapor deposition (CVD) growth on a liquid Cu surface, 30 types of twinned graphene polycrystals are predicted and most of them are observed experimentally.